Studi Anatomi Intestinum Krasum pada Kalong Kapauk (Pteropus vampyrus) - Yulfia Nelymalik Selan; Dwi Liliek Kusindarta; Tri Wahyu Pangestiningsih (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Pteropus vampyrus is one of the animal species that plays an important role in the ecosystem by spreading the seeds of the edible fruits. Feed variations on each animal greatly affect the digestive tract. This study was aimed to determine the anatomical structure of the large intestine. Five adult large flying foxes weighing 500-800 g were used as the sample in this study. Large intestines were embedded in paraffin and stained with H & E method. H & E staining resulted in the presence of intestinal villi on colon and rectum.